MEWARNAI HARI TUA DENGAN KETULUSAN HATI DAN KEHANGATAN CINTA PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA YOGYAKARTA - subandi, Subandi; MF Albashori, MF Albashori; Diana Sari Wijayanti, Irine; Andri Murdapa, Purnama; Moh Sholihin, Moh Sholihin (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
The Community Service Program (CSP) conducted for the elderly at the Tresna Werdha Social Home in Yogyakarta aims to provide care for the elderly, who generally experience mental changes that can lead to depression or stress and long-term health decline. Mental changes due to age are common in everyone. Therefore, attention is needed from the social environment. Therefore, there needs to be special attention to the welfare of the elderly, including efforts to create an environment that supports them physically, mentally, and socially. Devotion and social activities such as gymnastics and coloring can be effective solutions to improve the happiness and quality of life of the elderly, especially at the Tresna Werdha Social Home in Yogyakarta. Caring for the elderly is not only a personal responsibility, but also a social responsibility, and efforts like this need to be continuously encouraged to create a more inclusive and caring society for the elderly generation. The Community Service Program (PKM) activities carried out in collaboration between students and lecturers at Amayo are expected to have an impact on the welfare of the wider community.